Propuesta de implementación de un sistema de gestión de calidad según la NTC ISO/IEC 17025:2017 en el proceso de microbiología de un laboratorio de análisis ambiental (2018)
For the company MCS Consultoría y Monitoreo Ambiental, it is vital to expand its service portfolio, implementing the Microbiology process in order to improve the opportunity and quality of the service and thereby minimize the disadvantages that generate problems of a financial nature, delays in the delivery of results and, therefore, lower profits over time; Therefore, in this document we present a plan for the implementation of the microbiology process in which the requirements of the ISO 17025: 2017 standard are met in order to obtain accreditation and thus increase the profitability of the company as such.